Sleep architecture and epileptic characteristics of drug naïve patients in childhood absence epilepsy spectrum. A prospective study. (July 2018) - Dinopoulos, Argirios; Tsirouda, Maria A.; Bonakis, Anastasios; Pons, Roser; Pavlopoulou, Ioanna D.; Tsoumakas, Konstantinos
Highlights: High load epileptic activity before treatment is not unfavorable concerning absences. Persisting absence discharges may be deleterious for sleep architecture and stability. Absolute control of absences is accompanied by a more continuous, efficacious sleep. Abstract: Purpose: Childhood absence epilepsy (CAE) is an epileptic syndrome presenting between 2nd–10th years. The spells are elicited with hyperventilation (HV) while sleep seems to exacerbate the electrical activity. Our aim is to describe sleep architecture and its relationship with epileptic discharges (EDs) in patients with CAE, before treatment and one year later. Methods: Twenty-eight, drug-naive children were recruited (21 girls), mean age 90.1 ± 32.6 months. Routine-EEG and overnight EEG-polygraphy were conducted upon diagnosis and one year later. Patients were separated in two groups of similar mean age, according to their clinical response at the second recording: group A : children with absolute control of absences and group B : children with partial control. Sleep parameters, EDs and arousals were measured. The effect of medication on sleep parameters was examined, according to 2 groups: valproic-treated and non valproic-treated. Results: Group A showed significant improvement in total sleep time, REM-sleep latency, REM-sleep, arousals-number/hour and arousals-duration/hour between the two recordings. Comparing the two groups for each recording separately, group A initially demonstrated greater epileptic activity and worse sleep parameters, whereas in the second recording exhibited total elimination of the EDs and significantly less arousals. Group B demonstrated persisting EDs and slight deterioration in some sleep parameters during the second recording, despite the lower epileptic load initially. No significant difference was identified between valproic and non-valproic treated patients, regarding the effect on sleep parameters. Conclusion: Absolute control of absences and normalization of the electroencephalogram are accompanied by more continuous, stable and efficacious sleep in children with CAE.